Basic Psychological Needs at Work of Mental Health Professionals in Albania - Xhakollari, Lediana (Richtmann Publishing, 2013)
Research has supported the important role of meeting the needs of autonomy, competence and relatedness within theworkplace, in order to enhance wellbeing, including lowered stress, burnout, and anxiety and enhanced workplaceengagement The subjects of this study are mental health workers in Albania. This article reviews the meaning of quality ofwork life and analyses constructs of basic psychological needs at work based on Deci & Ryan model. The constructs of basicpsychological needs at work discussed are, the need for autonomy, the need for competence and the need for relatedness..This is mainly a quantitative study, with some elements of qualitative methods. Specifically, are used the scale measuringsatisfaction with basic psychological needs at work (adapted from the model of Deci & Ryan), interviews and observations. Atthe conclusion of the study came out that overall mental health workers are satisfied with their basic psychological needs atwork. Basic psychological need at work is positively related to all its constructs.